SADS-CoV nsp5 Inhibits Interferon Production by Targeting Kinase IKKε - Gaoli She; Chunhui Zhong; Yue Pan; Zexin Chen; Jingmin Li; Mingchong Li; Yufang Liu; Yongchang Cao; Xiaona Wei; Chunyi Xue (Microorganisms, 2025)
Swine acute diarrhea syndrome coronavirus (SADS-CoV), initially identified in China in February 2017, severely impacts the swine industry by causing lethal watery diarrhea in neonatal piglets. Understanding the molecular mechanism employed by SADS-CoV to evade the host’s immune defenses is of utmost importance. In this study, using the porcine ileum epithelial cell line IPI-FX as an in vitro model, we investigated the highly pathogenic SADS-CoV GDS04 strain and its nonstructural protein 5 (nsp5) for their roles in inhibiting interferon-beta (IFN-β) production. Our findings indicated that GDS04 inhibited poly(I:C)-induced IFN-β production by impeding the promoter activities of IRF3 and NF-κB. As a 3C-like protease, SADS-CoV nsp5 functioned as an interferon inhibitor by interacting with IKKε, reducing its protein abundance, and inhibiting its phosphorylation. This study enhances our understanding of the interaction between coronaviruses and their hosts, providing novel insights into the evasion of the immune system by coronaviruses.